Becoming more specific: Measuring and modeling teachers' perceived usefulness of ICT in the context of teaching and learning. (October 2015) - Scherer, Ronny; Siddiq, Fazilat; Teo, Timothy
Abstract: Studies on teachers' acceptance and use of information and communication technology (ICT) have revealed perceived usefulness to be a crucial determinant for integrating ICT in classrooms. In consequence, the present study focuses on teachers' perceived usefulness of ICT for teaching and learning and is aimed at describing its structure and relations to self-efficacy, ICT use, and teachers' age. By means of Bayesian analysis, we specified confirmatory factor-analytic and structural equation models to a large-scale data set of N = 1190 Norwegian teachers. Our results supported the hypothesized four-factor structure of teachers' perceived usefulness of ICT, signifying different facets of ICT-related teaching goals in classrooms. Moreover, it was possible to disentangle general and specific components of the construct in nested factor models. In support of existing research, we found positive relations to self-efficacy and ICT use, but a negative relation to teachers' age. Our study provides evidence on a multidimensional conceptualization of teachers' perceived usefulness of ICT for teaching and learning, and verifies the relations to teacher-related characteristics. Implications for the measurement and modeling of the construct, and future research directions are discussed. Highlights: Teachers' perceived usefulness of ICT for teaching and learning is multifaceted. A general factor and specific factors can be distinguished. Bayesian models with cross-loadings represent the structure of the construct. Perceived usefulness is positively related to self-efficacy and ICT use. Perceived usefulness is negatively related to teachers' age.